High‐Speed Counter‐Current Chromatography with an Online Storage Technique for the Preparative Isolation and Purification of Dihydroflavonoids from Sophora alopecuroides L. Issue 6 (6th June 2017) - Sun, Zhong‐Lin; He, Jian‐Ming; Lan, Jiang‐Er; Mu, Qing
Abstract: Introduction: High‐speed counter‐current chromatography (HSCCC) is an efficient and non‐absorption separation technique, but limitations still exist in simultaneous isolation of complex structures of natural products. Moreover, particular methods are various for different kinds of natural products. Objective: A novel HSCCC strategy combined with an online storage recycling elution (OSR‐CCC) technique was developed for the quick separation of naturally occurring dihydroflavonoids from the extract of the herb Sophora alopecuroides L . Methodology: In the separation procedure, a storage loop and two six‐port valves were connected to a HSCCC system. Effluent A was subjected to an online storage loop and then to recycling separation three times after effluent B was collected in head‐to‐tail mode. After completion of the recycling separation of effluent A, the elution was switched to tail‐to‐head mode to collect effluent C. A biphasic solvent system of n ‐hexane/ethyl acetate/methanol/water (9:6:6:8, v / v / v / v ) was used as the separation solvent during the whole elution. Results: Six constituents were isolated simultaneously from the extract (200 mg) of S. alopecuroides by running HSCCC non‐stop, and their purities were higher than 95.0%. Their structures were determined as the pterocarpan glycoside sophoratonkin (1) (10.0 mg) and five dihydroflavonoids, alopecurone F (2) (5.4 mg), lehmannin (3) (11.0 mg), alopecurone A (4) (35.0 mg), sophoraflavanone G (5) (21.0 mg), alopecurone B (6) (31.0 mg). Conclusion: This recycling HSCCC method combined with an online storage technique could be a rapid, effective and simple approach to isolate stilbene‐dihydroflavonoids from herbs of the Sophora genus simultaneously. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : HSCCC combined with an on‐line storage recycling (OSR) elution technique was employed. Reverse elution mode was used for decreasing the isolation cost ultimately. Six natural stilbene‐dihydroflavonoids were non‐stop isolated from a Sophora herb by running OSR‐HSCCC.